Lefkoşa Tarihi Kent Dokusunda “Selimiye Meydanı” / “Selimiye Square” Within the Historical City Texture of Nicosia - Turkan, Zihni; Özburak, Çimen (Journal of History Culture and Art Research, 2018)
ABSTRACT Selimiye Square, placed in the historical Selimiye neighborhood within the walled city of Nicosia, has become an important center, shaped with the architectural heritage of different cultures throughout the history of Cyprus. The creation of the square began with the building of the St. Sophia Cathedral of the Lusignan Period, at the beginning of the 1200s, and it developed as a religious center with the addition of St. Nicholas Church and the Archbishopric right after. Although not much development in the texture, a guest house built for travelers and pilgrims (The Venetian House) and the meeting place built for the priests of the cathedral (Chapter House), continued the process of creation of the square and the religious quality of the texture. During the Ottoman Period, which was an important era for the historical urban texture of Nicosia, Turkish Architecture, a new architectural style, was added to the surroundings of Selimiye Square. St. Sophia Cathedral was turned into a mosque with the addition of minarets, the Archbishopric and the building next to it were turned into Traditional Turkish Houses with alterations and additions, and St. Nicholas Church was turned into Bedesten (covered bazaar). With the addition of Sultan Mahmut Library and the Big and Small Medrese (madrasah), educational and business functions were added to the religious center; thus the creation of a historical environment and the boundaries of the square became clarified. The boundaries of the square were completed during the British Period with the construction of houses towards the west of the square and it gained the identity of a meeting place for the social activities of the city. During this period, the square was opened for vehicle traffic, and its texture, its religious and business center character were preserved. The periods of the Republic of Cyprus and the following Cyprus Turkish Administration years were a stagnant period for the creation and development of the square. During this period, the square was used as a place of ceremonies with the erection of the Fighters Monument in the east of the library. The buildings around the square underwent functional changes during the TRNC period, from 1983 to today, but the texture preserved its importance with its religious, educational, and business activities. With the new arrangements in 2001 within the scope of the pedestrianization project, an important meeting place was created for the social activities of the city. Thus, becoming an important center for the tourism and social life of the city with the mosque, cultural center, museum, folk arts atelier, restaurants, and bars, which all exist within this historical texture. ÖZ Lefkoşa Suriçi’nde, tarihi Selimiye Mahallesi’nde yer alan Selimiye Meydanı; Kıbrıs’ın tarihindeki farklı kültürlerin mimari mirasları ile biçimlenen önemli bir merkez olmuştur. Lüzinyanlar Dönemine ait St. Sophia Katedrali’nin, 1200’lü yılların başında burada inşa edilmesiyle başlayan meydan oluşumu, hemen sonrasında St. Nicholas Kilisesi ve Başpiskoposluk Binasının eklenmesi ile buranın bir dini merkez olarak gelişmesini yönlendirmiştir. Venedikliler Döneminde, dokuda fazla bir gelişme olmamakla birlikte, seyyahlar ve hacılar için yapılan misafirhane binası (Venedik Evi) ve katedralin rahipleri için yapılan toplantı binası (Chapter House), dokunun dini merkez niteliği ile meydanın oluşum sürecini devam ettirmiştir. Lefkoşa tarihi kent dokusunun gelişimi için önemli olduğundan, Selimiye Meydanı için de bir değişim dönemi olan Osmanlı Döneminde, Selimiye Meydanı çevresine yeni bir mimari olan Türk Mimarisi kazandırılmıştır. St. Sophia Katedrali, eklenen minarelerle camiye, Başpiskoposluk binası ve yanındaki bina, tadilât ve ilâvelerle Geleneksel Türk Evi’ne, St. Nicholas Kilisesi de Bedesten’e dönüştürülmüştür. Sultan Mahmut Kütüphanesi ile Büyük ve Küçük Medrese binalarının dokuya eklenmesiyle de dini merkeze eğitim ve ticaret işlevleri de katılımış; böylece tarihi çevre oluşumu ve meydan sınırları belirginleşmeye başlamıştır. İngiliz Döneminde, meydanın batı yönüne inşa edilen konutlarla meydan sınırları tamamlanmış ve kentin sosyal etkinlikleri için toplanma alanı kimliğini kazanmıştır. Bu dönemde meydan, araç trafiğine açılmış, çevre dokusu, dini ve eğitim merkezi özelliğini korumuştur. Kıbrıs Cumhuriyeti ve sonrasındaki Kıbrıs Türk Yönetimi Dönemleri, meydan oluşumu ve gelişimi için durgun bir dönem olmuştur. Bu dönemde, kütüphanenin doğu tarafına inşa edilen Mücahitler Anıtı ile meydan, tören alanı olarak da kullanılmıştır. 1983 yılından günümüze kadar olan KKTC Döneminde, meydan çevresindeki yapılar işlev değiştirmiş, fakat doku yine dini, ticari ve eğitim faaliyetleri ile önemini korumuştur. Yayalaştırma projesi kapsamında 2001 yılında meydanda yapılan yeni düzenleme ile kentin sosyal etkinlikleri için önemli bir buluşma alanı oluşturulmuş, tarihi dokuda yer alan cami, kültür merkezi, müze, halk sanatları atölyesi, lokanta, bar gibi işlevlerle de kentin turizmi ve sosyal yaşamı için önemli bir merkez olarak yaşam bulmuştur.